Proceedings of the 21th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2015
DOI: 10.1145/2783258.2788609
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Future Scientific Discoveries Based on a Networked Analysis of the Past Literature

Abstract: We present KnIT, the Knowledge Integration Toolkit, a system for accelerating scientific discovery and predicting previously unknown protein-protein interactions. Such predictions enrich biological research and are pertinent to drug discovery and the understanding of disease. Unlike a prior study, KnIT is now fully automated and demonstrably scalable. It extracts information from the scientific literature, automatically identifying direct and indirect references to protein interactions, which is knowledge that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…PKN1 and NEK1 were 2 kinases highly ranked by Watson as having the potential to phosphorylate P53. 32 Lab experiments at Baylor College of Medicine suggested that these kinases could phosphorylate P53 in both in vitro experiments and in tests on human cells. Further experiments are being conducted to test the activity of these kinases in organisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PKN1 and NEK1 were 2 kinases highly ranked by Watson as having the potential to phosphorylate P53. 32 Lab experiments at Baylor College of Medicine suggested that these kinases could phosphorylate P53 in both in vitro experiments and in tests on human cells. Further experiments are being conducted to test the activity of these kinases in organisms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to visualizing expressed patterns, machine learning and predictive analytics generate hypotheses about relationships; in effect "inferring" novel connections not yet supported by overt statements in the literature as was done in a project with Baylor College of Medicine where hypotheses of new kinases that could phosphorylate TP53 were generated out of existing medical literature. 31,32 If the observation and interpretation of concepts are the foundation for discovery in a human's cognitive process, the next step is evaluation. 30 Humans have the ability to evaluate evidence and apply it to solve different types of problems.…”
Section: Part Iii: Cognitive Technologies: a New Way To Aggregate Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, selecting the suitable data type in the papers in crucial as they represent different perspectives (Lee et al, 2015) and information content (Kostoff et al, 2004) and mainly depends on the objective of the research. Furthermore, Nagarajan et al (2015) have discovered that the LBD performance mainly depends on the richness of the information being used. Apart from research papers, several approaches have experimented the LBD process with other traditional data types such as patents and clinical case reports.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…For example, some studies (Rastegar-Mojarad et al, 2015;Cheung, Ouellette & Wasserman, 2012) have used drug-disease interactions in Comparative Toxicogenomics Database (CTD) to validate their results. Similarly, other databases such as SIDER2 (Shang et al, 2014), GEO (Faro, Giordano & Spampinato, 2011), GAD (Seki & Mostafa, 2009), StringDB (Nagarajan et al, 2015) have also been used for validation.…”
Section: Replicated Discovery Past Studiesmentioning
confidence: 99%